2009
DOI: 10.1016/j.jneuroim.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzyme dysfunction in monocytes and CSF of Hispanic women with HIV-associated cognitive impairment

Abstract: HIV-associated cognitive neurological disorders (HAND) prevail in the antiretroviral therapy era. Proteomics analysis of CSF revealed expression of Cu/Zn superoxide dismutase (Cu/Zn SOD) in Hispanic women with cognitive impairment (CI). We tested the hypothesis that there is reduced capacity of antioxidant enzymes in CI by measures of expression and activity of Cu/Zn SOD, catalase, and Se-glutathione peroxidase in HAND. Our results showed that the function of these antioxidants was decreased in the CSF and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…In the post-HAART era, female gender as a predictor for progression of HAND has not been previously reported. This may be in part owing to a finding that women with HAND have decreased function and activity of antioxidant enzymes in CSF and monocytes, thus possibly resulting in more oxidative stress in the CNS and thereby promoting peroxynitrite formation and neuronal damage [31,32]. On further analysis of this subset, we did find that women had significantly fewer years of education compared with men, which may explain their worsening HAND status.…”
Section: Discussionmentioning
confidence: 79%
“…In the post-HAART era, female gender as a predictor for progression of HAND has not been previously reported. This may be in part owing to a finding that women with HAND have decreased function and activity of antioxidant enzymes in CSF and monocytes, thus possibly resulting in more oxidative stress in the CNS and thereby promoting peroxynitrite formation and neuronal damage [31,32]. On further analysis of this subset, we did find that women had significantly fewer years of education compared with men, which may explain their worsening HAND status.…”
Section: Discussionmentioning
confidence: 79%
“…Several reports indicate that oxidative stress plays a major role in neuronal damage and cognitive disorders in HIV-infected patients. 62,63 In this study, we observed that reduced oxidative stress could be due to the decreased HIV infection because of release of TIMP1 from the MNP NF. We also observed the effect of free TIMP1 and MNP-bound TIMP1 exposure on the recovery of spine density in HIV-infected neuronal cells.…”
mentioning
confidence: 65%
“…Similar results were obtained in the CSF of HAND patients and in HIV seropositive patients that are cocaine users where cathepsin B secretion and activity remained at the same levels between experimental and control groups. It has been established that HIV-1 transforms the monocyte plasma membrane proteome (Kadiu et al 2009) and proteomics analysis of CSF demonstrated that reduction of antioxidants enzymes such as Cu/Zn SOD and GPx, have been associated with disease severity (Laspiur et al 2007; Velazquez et al 2009; Angel et al 2012). It is quite possible that an antioxidant imbalance could promote secretion and neurotoxic activity of cathepsin B in the CNS.…”
Section: Discussionmentioning
confidence: 99%